Understanding the paradox between tragedies of the commons and the anticommons: From a cognitive psychology perspective - Yang, Xiaowei; Yang, Shiqi; Wang, Yuejin; Zhang, Shuyu; Luo, Songmei (Frontiers in Psychology, 2022)
The tragedy of the commons refers to the overuse of resources which are rival in consumption but lack excludability and refers to rent dissipation. While the tragedy of the anticommons is a newly found tragedy, which is closely connected with underuse of resources that are rival in consumption and with too strong excludability. The prior studies proved that the tragedy of the commons and the tragedy of the anticommons are symmetric from the perspective of pure mathematics, especially the game theory, which was later refuted by research based on behavioral economics experiments. According to them, the tragedy of the anticommons is severer than the tragedy of the commons. The asymmetry of the tragedy of the commons and the tragedy of the anticommons is a paradox by these different research methods. This paradox shows that there are imperfections in the completely rational economic man hypothesis set up by neoclassical economics. Based on Simon's bounded rationality, Kahneman and Tversky's prospect theory, value function, Thaler's mental accounting, endowment effect and other cognitive psychological tools, this study clearly shows that agents' decision-making process is not just based on the marginal benefit and marginal cost analysis advocated by traditional neoclassical economists. Agents’ decision-making is a process in which agents selectively absorb, code the objective marginal revenue and marginal cost, and feed relevant information to their brain. Therefore, what plays a directly decisive role is not the objective marginal revenue and marginal cost per se. Still, the mentally perceived subjective utility of marginal revenue and marginal cost by the human brain. Followed by this research clue, the paradox between the tragedy of the commons and the tragedy of the anticommons is elucidated from the perspective of cognitive psychology.